2016
DOI: 10.5194/angeo-34-1031-2016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aerosol absorption properties and transport over North Africa and the Middle East using AERONET data

Abstract: Abstract. In this paper particle categorization and absorption properties were discussed to understand transport mechanisms at different geographic locations and possible radiative impacts on climate. The long-term Aerosol Robotic Network (AERONET) data set (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) is used to estimate aerosol optical depth (AOD), single scattering albedo (SSA), and the absorption Ångström exponent (α abs ) at eight locations in North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…It was found that the average daily concentrations in Dhahran, Khobar, and Dammam are ∼177 g/m 3 , 379 g/m 3 , and 126 g/m 3 , respectively. Particles shapes were found to vary from irregular, platy, spherical, rod-like, and angular.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the average daily concentrations in Dhahran, Khobar, and Dammam are ∼177 g/m 3 , 379 g/m 3 , and 126 g/m 3 , respectively. Particles shapes were found to vary from irregular, platy, spherical, rod-like, and angular.…”
Section: Resultsmentioning
confidence: 99%
“…Equivalent Aerodynamic Diameters (EAD) method is the basic technique used to classify PM [1], where particles could be classified into PM 10 , PM 2.5 , and PM 1.0 representing their 10, 2.5, and 1 m sizes, respectively [2,3]. PM 10 particles are referred to as "inhalables" and usually trapped in mucus linings and may cause significant health effects to the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a lack of rainfall, the role of precipitation is limited in affecting aerosol characteristics over KSA; however, dust transport and local anthropogenic emissions play a major role in influencing aerosol properties. Moreover, the satellite and ground-based data reveal that the pronounced increase in aerosol loadings is due to the increase in anthropogenic activities over the central and eastern regions of KSA [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The large increase in anthropogenic aerosols over KSA has a significant impact on the regional climate and on human health [4,5]. Detailed aerosol categorization across several Aerosol Robotic Network (AERONET) stations located in the Middle East and North Africa during the period 1995-2015 was investigated in [6]. The dominance of aerosol particles associated with major dust events at different locations over KSA was observed.…”
Section: Introductionmentioning
confidence: 99%